John Dewey ant the learning from experience (Revista Apotheke, 2021)
The impact of John Dewey’s theory on education is undeniable. His ideas questioned traditional pedagogical concepts and stood against centuries of an educational process in which knowledge was centered on content transmitted in a ready and closed manner. Dewey pointed to the need for the teaching-learning process to be centered on the experiences lived and on the re-signification of these experiences in a way similar to an artistic practice. He also advocated the importance of encouraging the student’s role and his ability to question and reconstruct knowledge. This article analyzes the educational thought of John Dewey focusing on some of the main concepts of his theory such as the continuity principle, the experience concept, the idea of activity and his concept of reconstruction.
Keywords: John Dewey; education; learning; art; experience